Tissue Engineering: Reconfigurable Microphysiological Systems for Modeling Innervation and Multitissue Interactions (Adv. Biosys. 9/2020). Issue 9 (3rd September 2020) - Soucy, Jonathan R.; Bindas, Adam J.; Brady, Ryan; Torregrosa, Tess; Denoncourt, Cailey M.; Hosic, Sanjin; Dai, Guohao; Koppes, Abigail N.; Koppes, Ryan A.
Abstract : To overcome the limitations of traditional organ chips, in article number 2000133, Ryan A. Koppes and co‐workers have implemented a "cut and assemble" manufacturing technique to exploit the meniscus pinning effect, via GelPins, to constrain 3D biomaterials. These GelPins enable the formation of discrete, yet contiguous hydrogel structures in both x‐y and z planes within custom microfluidic devices, facilitating future investigation of innervation and heterogenous tissue interactions.